Knowledge and awareness about cervical Cancer and its Prevention among Women Attending at Out patient Department of Dhaka Medical College Hospital (Journal of Shaheed Suhrawardy Medical College, 2018)
The purpose of this study was to assess the knowledge and awareness regarding cervical cancer and its prevention among women attending at out patient department of Dhaka Medical College Hospital. A qualitative study was undertaken using face to face in depth interviews from January 2015 to July 2015 .Among 229 women mean age 34.07±7.92 ,from 18 to 60 years were observed. Awareness and knowledge about cervical cancer was very poor which was about 25.3%. Knowledge was high among women coming from high socioeconomic condition which was 31.5% (p=0.03). Participants who were highly educated had more knowledge about 83.3% (